The Influence of Poster Media on Increasing Knowledge about Anemia among Female Students at Arrahmah Modern Islamic Boarding School - Ulya, Happy Arini Zulfatul; Sodik, Mohammad Ali; Suprapto, Sentot Imam; Yuliawati, Riza (Journal of Global Research in Public Health, 2025)
Anemia is a common health problem among adolescent girls, affecting daily activities and academic performance. Low knowledge about anemia is one of the main contributing factors to its high prevalence.   This study aims to determine the effectiveness of poster media in increasing knowledge about anemia among female students at the Arrahmah Modern Islamic Boarding School. This study employed a pre-experimental design with a one group pretest-posttest approach. A total of 66 students at Modern Arrahmah Islamic Boarding School were selected using simple random sampling. A structured questionnaire was used for pretest and posttest, and data were analyzed using the McNemar test.  Before the intervention, most respondents had moderate knowledge (60.6%), which increased to 87.9% in the high category after the intervention. The McNemar test showed a Chi-Square value of 22.132 with a p-value = 0.000 (p < 0.05).  Poster media significantly improves students' knowledge about anemia. It is recommended as a simple yet effective educational tool, especially in Islamic boarding school environments.